PELAKSANAAN PEMBELAJARAN SENI BUDAYA PADA KELAS X SMKN 2 KARANG BARU ACEH TAMIANG - NURMAINI, Dr. Ramalis Hakim, M.Pd, Drs. Ajusril S (Universitas Negeri Padang, 2013)
This study aims to discribe the implementation of the Cultural Art Learning in class X SMKN 2 Karang Baru Aceh Tamiang about: 1) Organization of learning, 2) Submission of learning, 3) learning management. The data collection activities include the collection of data obtained through direct observation, interviews, archives and documents. The findings of the study are: 1) the organization of the learning content by GS on every class has implemented the strategy of micro and macro strategies. 2) delivery of learning undertaken by GS looks had engged in media containing components of learning, student interaction and media, and form of learning. 3) teachers have implemented a learning management that includes scheduling the use of intructional strategies, note taking students’ progress, and management of student motivation. Cultural art learning activities that teacher have implemented learning management strategies. But teacher do not learn to control. Kata kunci: pembelajaran, seni budaya, SMKN 2 karang baru